Investigation of relation between Clostridium colonization and nutrient consumption in intestinal flora in athletes and sedentary men - Genç, Ayça; Tutkun, Erkut; Acar, Hakan; Zorba, Erdal (Progress in Nutrition, 2020)
The aim of this study is to investigate the relation between clostridium colonization and frequency of nutrient consumption in intestinal flora of athletes and sedentary men. Fifteen volunteer males aged between 18- 24 participated in the study and the participants were divided into 3 groups; the first group (n = 5); consisted of athletes who play football in the professional league and have regular training, the second group (n=5); amateur league football players and regular training athletes and the third group (n=5); 5 men who were physically inactive (sedentary). In this study, 1 stool sample was taken from all subjects and metagenomic analysis was analyzed using the Illumina MiSeq analyzer with the New Generation Sequencing method. In addition, “Nutrition Consumption Frequency” questionnaire was applied to determine the eating habits of the subjects. For statistical analysis of the findings, the package program of Minitab 17 and SPSS 24 was used and the significance level was taken as p<0.05. It was determined that meat, eggs, clumps (protein group) and yoghurt, milk, ayran (dairy product) were the most consumed food group while the bread, cereals (carbohydrate group), sweet and fatty foods were the least consumed food group by the Professional football players. The dessert, fatty foods, bread and cereal products (carbonhydrate group) were the most consumed food group while the meat, eggs, legume (protein group) and yoghurt, milk and ayran (dairy product) were the least consumed food group by the amateur football players. The most consumed food group of the sedentary individuals was the group of vegetables and fruits and bread, the cereals (carbohydrate group), while the least consumed foods are milk, yogurt, ayran (group of dairy products) and meat, eggs, rind (protein group). Although there are differences in nutrient consumption among professional and amateur footballers and sedentary individuals, no statistically significant difference was found in clostridium genus intestinal flora (p>0.05). It was determined that professional football players have lower clostridium intestinal flora than amateur football players and sedentary group. We think that this difference is caused by the difference between the nutrition habits together with exercise, and that exercise supported by the healthy nutrition program will increase the development of beneficial flora in the intestine and contribute to the suppression of pathogen species.